(untitled) (Symposium on Life and Environmental Sciences, 2026)
This study analyzes the impact of digital transformation on productivity growth in global apparel value chains. The study focuses on the application of advanced technologies such as artificial intelligence, automation systems, and digital supply chain platforms in the textile and garment industry. In the context of globalization, apparel production is organized through complex international networks, where efficiency depends on coordination, information flow, and technological integration. The research is based on the analysis of international reports and academic literature from organizations such as McKinsey Global Institute, ILO, and World Bank. The findings show that digital transformation improves productivity by reducing production costs, minimizing delays, and increasing flexibility in manufacturing systems. In addition, automation and data-driven decision-making enhance quality control and resource optimization. The study concludes that digital technologies are a key factor in improving competitiveness and long-term efficiency in the global apparel industry.